2008
DOI: 10.1136/sti.2007.028217
|View full text |Cite
|
Sign up to set email alerts
|

Routine HIV testing in the context of syndromic management of sexually transmitted infections: outcomes of the first phase of a training programme in Botswana

Abstract: Objective:In 2004, the Ministry of Health adopted revised protocols for the syndromic management of sexually transmitted infections (STI) that included routine HIV testing. A training programme for providers was developed on the revised protocols that featured interactive case studies and training videos. An objective of the first phase of the training programme was to test its effect on four measures of clinical practice: (1) routine HIV testing; (2) performance of physical examination; (3) risk-reduction cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The absolute increase in HIV testing rate of nearly 14% is smaller than the difference of 20% anticipated prior to the study, though it is similar to increases reported in prior studies in South Africa (13% increase for TB patients) [16] and Botswana (19% increase for STI patients) [27]. This study may have underestimated the impact of the PITC intervention as two practice shifts could have narrowed the difference between control and intervention clinic outcomes in the study setting.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The absolute increase in HIV testing rate of nearly 14% is smaller than the difference of 20% anticipated prior to the study, though it is similar to increases reported in prior studies in South Africa (13% increase for TB patients) [16] and Botswana (19% increase for STI patients) [27]. This study may have underestimated the impact of the PITC intervention as two practice shifts could have narrowed the difference between control and intervention clinic outcomes in the study setting.…”
Section: Discussionsupporting
confidence: 77%
“…The evidence for PITC with STI patients is limited to a few quasi-experimental studies in the UK and the Netherlands [ 20 , 21 , 25 , 26 ], and one controlled trial in Sub-Saharan Africa [ 27 ]. The European trials report significant increases in HIV testing for STI patients, although a recent UK study with low-risk STI patients showed that there was a significant increase in the offer of testing, not in the proportion of patients who accepted testing [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient satisfaction is increasingly recognized as an essential component of evaluating health systems in developing countries [26]. While a few studies have found significant effects of health interventions in Africa on improving patient satisfaction [27][28][29][30], patient satisfaction is still infrequently measured in assessing the success of health interventions in resource-limited settings. This study demonstrates both the feasibility and utility of measuring patient satisfaction as a critical component of QI initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have reported on the effectiveness of classroom-based STI syndromic management training, 9 14 15 but less is known about the effectiveness of clinic-based programmes. In general, evidence shows that online learning is as effective as classroom methods.…”
Section: Introductionmentioning
confidence: 99%